Adapting and Implementing a Community Program to Improve Retention in Care among Patients with HIV in Southern Haiti: "Group of 6". (7th December 2014) - Naslund, John A.; Dionne-Odom, Jodie; Junior Destiné, Cléonas; Jogerst, Kristen M.; Renold Sénécharles, Redouin; Jean Louis, Michelande; Desir, Jasmin; Néptune Ledan, Yvette; Beauséjour, Jude Ronald; Charles, Roland; Werbel, Alice; Talbot, Elizabeth A.; et al.
Abstract : Objective . In Mozambique, a patient-led Community ART Group model developed by Médecins Sans Frontières improved retention in care and adherence to antiretroviral therapy (ART) among persons with HIV. We describe the adaptation and implementation of this model within the HIV clinic located in the largest public hospital in Haiti's Southern Department. Methods . Our adapted model was named Group of 6. Hospital staff enabled stable patients with HIV receiving ART to form community groups with 4–6 members to facilitate monthly ART distribution, track progress and adherence, and provide support. Implementation outcomes included recruitment success, participant retention, group completion of monthly monitoring forms, and satisfaction surveys. Results . Over one year, 80 patients from nine communities enrolled into 15 groups. Six participants left to receive HIV care elsewhere, two moved away, and one died of a non-HIV condition. Group members successfully completed monthly ART distribution and returned 85.6% of the monthly monitoring forms. Members reported that Group of 6 made their HIV management easier and hospital staff reported that it reduced their workload. Conclusions . We report successful adaptation and implementation of a validated community HIV-care model in Southern Haiti. Group of 6 can reduce barriers to ART adherence, and will be integrated as a routine care option.